Exogenous phthalanilic acid induces resistance to drought stress in pepper seedlings (Capsicum annuum L.) - Lu, Xiaopeng; Wu, Qiong; Nie, Keyi; Wu, Hua; Chen, Guangyou; Wang, Jun; Ma, Zhiqing (Frontiers in Plant Science, 2023)
Drought stress (DS) is one of the main abiotic negative factors for plants. Phthalanilic acid (PPA), as a plant growth regulator, can promote the growth and development of crops. In order to evaluate the ideal application concentration and frequency of PPA-induced drought resistance in pepper (Capsicum annuum) seedlings, the concentration of PPA was 133.3 mg·L−1; 200.0 mg·L−1; 266.7 mg·L−1, and some key indicators were investigated, including leaf wilting index (LWI), relative water content (RWC), and malondialdehyde (MDA). We found that the LWI and RWC in the PPA-applied pepper leaves under light drought stress (LDS) and moderate drought stress (MDS) were all elevated, while MDA contents were decreased. To better understand how PPA makes pepper drought resistant, we examined the photosynthetic characteristics, growth parameters, antioxidant activities, and osmotic substances in pepper seedlings treated twice with PPA at a concentration of 133.3 mg·L−1 under LDS, MDS, and severe drought stress (SDS). Results showed that PPA increased the chlorophyll, plant height, stem diameter, root-shoot ratio, and seedling index of pepper leaves under LDS, MDS, and SDS. The net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci), transpiration rates (Tr), and water-use efficiency (WUE) in the PPA-treated pepper leaves under LDS and MDS were improved, while their stomatal limitation (Ls) were reduced. PPA also boosted the activities of enzymatic antioxidants (superoxide dismutase, catalase, and peroxidase), as well as enhanced the accumulation of osmotic substances such as soluble sugar, soluble protein, and free proline in pepper leaves under LDS, MDS, and SDS. Thus, PPA can alleviate the growth inhibition and damage to pepper seedlings caused by DS, and the PPA-mediated efficacy may be associated with the improvement in PPA-mediated antioxidant activities, Pn, and accumulation of osmotic substances.